Organisational climate as a predictor of workforce performance in the Malaysian higher education institutions - Musah, Mohammed Borhandden; Mohd Ali, Hairuddin; Vazhathodi Al-Hudawi, Shafeeq Hussain; Mohd Tahir, Lokman; Daud, Khadijah; Said, Hamdan; Kamil, Naail Mohammed (Emerald Group Publishing Ltd., 2016)
This study aims to investigate whether organisational climate (OC) predicts academic staff performance at Malaysian higher education institutions (HEIs). The study equally aims at validating the psychometric properties of OC and workforce performance (WFP) constructs. Design/methodology/approach: Survey questionnaires were administered to 800 academic staff of eight selected HEIs. Principal component analysis, confirmatory factor analysis, full-fledged structural equation modelling and multiple regression analysis were performed to explore the underlying factors and test the factorial validity of the constructs. Findings: The analysis yielded a five-factor index for the OC construct, whereas the WFP construct comprised two factors. The findings reveal a strong predictive causal effect between OC and WFP. These results suggest that establishing a positive OC enhances academic staff performance. Furthermore, the hypothesised model adds new knowledge to the literature of OC, from the Malaysian context, which could be used to predict WFP at the tertiary level. Practical implications: The study concludes by discussing the theoretical and practical implications of the findings for HEIs. Originality/value: This paper makes a significant contribution to the understanding of how OC could be used as an effective instrument in improving academic staff performance in the context of Malaysian HEIs.